Determinación del antígeno carcinoembrionario, como indicador de recidiva tumoral en pacientes con cáncer colorrectal que acuden al área de gastroenterología de Solca-Loja. - Aleaga Trujillo, María Belén (2013)
Colorectal cancer is one of the tumors that ranks third in frequency in men and the second in women, so it represents a major public health problem worldwide. In Ecuador in 2009 the number of National Cancer Registry of SOLCA indicates that 14 out of 100 Ecuadorian died of cancer. According to PAHO, Ecuador has one of the highest annual rates in Latin America with 11.6 percent, the most frequent cancers by sex in the country are: breast women 35.4%, skin 32 % 17% cervix, thyroid 15.5% 14.5% stomach. In men the prostate are 50.1% 22.7% stomach; lymphatics 12.4% 10.8% leukemia, colon and rectum 9.9%. According to research, over 50% of patients with colorectal cancer will have metastatic disease or disease locally advanced unresectable sometime during the course of the disease , there is a relationship between the elevation of the CEA tumor recurrence after surgery and with 80% sensitivity and specificity of 70 % for this reason this descriptive research , conducted in 67 patients with colorectal cancer (CRC ) treated in Loja - SOLCA during January 2012 to may 2013, allowed the observation of a 52.24 % of the affected are male and 47.76 % of the female , most ( 53.8 % ) aged between 58-77 years, with 18 % of recurrent cases , thus confirmed that the disease affects their most patients over 50 years of age of which 12 recurred , showing 16.67% CEA concentrations greater than 33 ng/ml considered as an indicator of tumor recurrence , while the remaining 83.33 % had values below 33 ng / ml , for this reason it was considered that CEA is not recommended as a screening method because of its low sensitivity and specificity, but it is important in monitoring the CCR and will determine in conjunction with tumor stage, treatment this pathology . And as a contribution to the community in order to prevent and provide information about the disease is distributed an information leaflet for patients attending the Gastroenterology Area SOLCA-Loja, during the month of June, 2013. Keywords: CEA, colorectal cancer, follow-up, recurrence.